Tumor-specific cytosol-penetrating antibodies for antigen- and TME-dependent intracellular cargo delivery - Carolin Sophie Dombrowsky; Felix Klaus Geyer; Diana Zakharchuk; Harald Kolmar (Molecular Therapy: Oncology)
Although a considerable number of disease-related biomolecular interactions occur in the cytosol, therapeutic and diagnostic application of target-specific binding proteins is largely confined to surface-exposed or extracellular targets. Therefore, protein-cargo delivery approaches, including cell-penetrating peptides and cytosol-penetrating antibodies, are being explored to overcome this limitation. In this context, we have developed a modular approach for cytosolic penetration of tumor cells based on bispecific antibodies containing a masked cytosol-penetrating Fab on one arm and a tumor-targeting scFv linked via an endosomal cleavable linker on the other arm. The relevance of the antigen-specific binding, internalization, and cytosolic cargo delivery was demonstrated in several in vitro assays using different cell lines with anti-B7-H3 scFv, the well-characterized trastuzumab (HER2), and inotuzumab (CD22) as examples. In addition, presence of the masking moiety to prevent non-specific surface binding, as well as the activation of cytosol-penetrating capabilities in the tumor microenvironment upon release by tumor-specific proteases was confirmed using the catalytic domain of Pseudomonas exotoxin as model cargo for cytosol delivery. Tumor microenvironment-dependent as well as tumor-associated antigen-specific cytosol-penetrating antibodies of the type developed here have the potential to serve as a modular platform to deliver macromolecular cargoes for addressing intracellular targets in tumor cells.